tudy of morphological variability of Pinus sylvestris leaves collected in the Karaganda region - Tuleshova К.А.; Kali А.К.; Kyzdarova, D.K.; Keikin Е.К. (Fundamental and Experimental Biology, 2022)
Bioindication using morphological indicators of plant leaves is an urgent direction for a quick and inexpensive assessment of environmental pollution. Karaganda region is an industrial region with a high level of emissions due to the activities of mining and metallurgical enterprises. The purpose of this paper to study the morphometric indicators of Pinus sylvestris needles collected in various places of growth in the Karaganda region (Central Kazakhstan): the cities of Karaganda, Temirtau, Satpayev, Balkhash, Zhezkazgan, Ulytau vil-lage. This article presents the study results of morphometric indicators of pine needles with an assessment of the appearance, length, width, thickness of needles, and average rotation around its own axis. It is found that in more contaminated areas, minimum values of sheet length and width, maximum values of average rotation around the axis, and the coefficient of variation of features are observed. Maximum values of sheet length and width, minimum degree of variation of studied features are noted in low-polluted areas. The thickness of the sheet does not reveal a reliable difference in the variants of the experience. The obtained data can be used for bioindication of environmental pollution.